Allsides farmers pre-cooperative a socio-economic assessment - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The Allsides Pilot Development project, is a joint venture undertaken by Government of Jamaica and the IICA in "Hillsides Farming Study and Implementation" in the allsides area of the parish of trelawny.